2020
DOI: 10.1371/journal.pgen.1009001
|View full text |Cite
|
Sign up to set email alerts
|

Excess crossovers impede faithful meiotic chromosome segregation in C. elegans

Abstract: During meiosis, diploid organisms reduce their chromosome number by half to generate haploid gametes. This process depends on the repair of double strand DNA breaks as crossover recombination events between homologous chromosomes, which hold homologs together to ensure their proper segregation to opposite spindle poles during the first meiotic division. Although most organisms are limited in the number of crossovers between homologs by a phenomenon called crossover interference, the consequences of excess inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 67 publications
(143 reference statements)
2
22
0
Order By: Relevance
“…For instance, AIR-2 and other CPC components are often mispatterned in the absence of AIR-2 kinase activity ( Fig 1 and S3 Fig ), so these chromosome structure defects could cause the failure to assemble the RC. However, bivalents containing multiple chiasmata have major CPC patterning defects but can still assemble RC components, demonstrating that proper chromosome structure is not a pre-requisite for RC assembly [ 17 ]. Similarly, it is possible that failure to assemble the RC in the AIR-2 KD TG strain causes the later spindle assembly and chromosome segregation defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, AIR-2 and other CPC components are often mispatterned in the absence of AIR-2 kinase activity ( Fig 1 and S3 Fig ), so these chromosome structure defects could cause the failure to assemble the RC. However, bivalents containing multiple chiasmata have major CPC patterning defects but can still assemble RC components, demonstrating that proper chromosome structure is not a pre-requisite for RC assembly [ 17 ]. Similarly, it is possible that failure to assemble the RC in the AIR-2 KD TG strain causes the later spindle assembly and chromosome segregation defects.…”
Section: Discussionmentioning
confidence: 99%
“…AIR-2 is also essential for the assembly of the "ring complex" (RC), which encircles the center of each bivalent during Meiosis I (and the sister-chromatid interface during Meiosis II) [13][14][15][16]. The CPC is required for localization of all other known RC components [14,15], and chromosomes lacking RCs or with improperly patterned RCs show defects in chromosome congression [13,17]. Finally, AIR-2 depletion has been reported to cause spindle defects in C. elegans oocytes [6,8,14,15], although what part of the spindle assembly pathway is affected has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…A study in C. elegans found that interference plays a key role in ensuring proper chromosome segregation by limiting the number of crossovers per homolog (Hollis et al, 2020); however, this may be a problem unique to organisms without defined centromeres. Interference may serve to limit the number of crossovers, but in Arabidopsis, increasing crossovers by three-sixfold has no apparent negative effect on fertility or chromosome segregation (Crismani et al, 2012;Girard et al, 2015).…”
Section: Interference and Assurancementioning
confidence: 99%
“…Thus, this particular solution to the problem of segregating holocentric chromosomes in meiosis appears to predate the Rhabditine radiation. This pathway relies on the formation of two bivalent "arms" with reciprocal functions, which in turn depends on strict crossover interference; multiple crossovers "confuse" the system and lead to frequent missegregation (Hollis et al, 2020). We expect that these two features of meiosis are widely shared among and perhaps beyond Clade V nematodes.…”
Section: Comparative Analysis Of Meiosis Reveals Variations and Similarities Within The Nematode Lineagementioning
confidence: 99%